Does India use development finance to compete with China?: a subnational analysis - Asmus, Gerda; Eichenauer, Vera; Fuchs, Andreas; Parks, Bradley (Discussion papers, 2021)
China and India increasingly provide aid and credit to developing countries. This paper explores whether India uses these financial instruments to compete for geopolitical and commercial in uence with China (and vice versa). To do so, we build a new geocoded dataset of Indian government-financed projects abroad between 2007 and 2014 and combine it with data on Chinese government-financed projects. Our regression results for 2,333 provinces within 123 countries demonstrate that India's Exim Bank is significantly more likely to locate a project in a given jurisdiction if China provided government financing there in the previous year. Since this effect is more pronounced in countries where China has made public opinion gains relative to India and where both lenders have a similar export structure, we interpret this as evidence of India competing with China. By contrast, we do not find evidence that China uses official aid or credit to compete with India through co-located projects.
Keywords: Graue Literatur